Angiotensin II Type 1 Receptor Tachyphylaxis Is Defined by Agonist Residence Time. Issue 1 (January 2022) - Duarte, Diego A.; Parreiras-e-Silva, Lucas T.; Oliveira, Eduardo B.; Bouvier, Michel; Costa-Neto, Claudio M.
Abstract : Several GPCRs (G-protein–coupled receptors) have been reported to exhibit tachyphylaxis, which is an acute loss of functional receptor response after repeated stimuli with an agonist. GPCRs are important clinical targets for a wide range of disorders. Therefore, elucidation of the ligand features that contribute to receptor tachyphylaxis and signaling events underlying this phenomenon is important for drug discovery and development. In this study, we examined the role of ligand-binding kinetics in the tachyphylaxis of AT1 R (angiotensin II type 1 receptor) using bioluminescence resonance energy transfer assays to monitor signaling events under both kinetic and equilibrium conditions. We investigated AT1 R signal transduction and translocation promoted by the endogenous tachyphylactic agonist Ang II (angiotensin II) and its analogs, described previously for inducing reduced receptor tachyphylaxis. Estimation of binding kinetic parameters of the ligands revealed that the residence time of Ang II was higher than that of the analogs, resulting in more sustained Gq protein activation and recruitment of β-arrestin than that promoted by the analogs. Furthermore, we observed that Ang II led to more sustained internalization of the receptor, thereby retarding its recycling to the plasma membrane and preventing further receptor responses. These results show that the apparent lack of tachyphylaxis in the studied analogs resulted from their short residence time at the AT1 R. In addition, our data highlight the relevance of complete characterization of novel GPCR drug candidates, taking into account their receptor binding kinetics as well. Abstract : Supplemental Digital Content is available in the text.